2012
DOI: 10.1017/s0269889712000233
|View full text |Cite
|
Sign up to set email alerts
|

Science Inside Law: The Making of a New Patent Class in the International Patent Classification

Abstract: ArgumentRecent studies of patents have argued that the very materiality and techniques of legal media, such as the written patent document, are vital for the legal construction of a patentable invention. Developing the centrality placed on patent documents further, it becomes important to understand how these documents are ordered and mobilized. Patent classification answers the necessity of making the virtual nature of textual claims practicable by linking written inscription to bureaucracy. Here, the epistem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 56 publications
(74 reference statements)
0
17
0
Order By: Relevance
“…Previous studies have shown that the scientific-technological invention is not identical to its legal representation and that there are divergences in what can and cannot be claimed as a patentable invention in law. 47 Despite the feeling of ghostliness of the invention and its decomposition and ghost-like presence across different digital technological platforms, the feeling of immateriality and the appearance of a virtual reality of inventions in database networks should not be overestimated. The previous discussion has tried to hint at the enormity of the data infrastructure which underpins patents' electronic textuality in terms of storage hardware, software and networks of people and information.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the scientific-technological invention is not identical to its legal representation and that there are divergences in what can and cannot be claimed as a patentable invention in law. 47 Despite the feeling of ghostliness of the invention and its decomposition and ghost-like presence across different digital technological platforms, the feeling of immateriality and the appearance of a virtual reality of inventions in database networks should not be overestimated. The previous discussion has tried to hint at the enormity of the data infrastructure which underpins patents' electronic textuality in terms of storage hardware, software and networks of people and information.…”
Section: Resultsmentioning
confidence: 99%
“…7 Patents and the inventions that these property rights would cover needed to be recorded in writing and accounted for by their classification, storage and access. 8 This was because a patent owner as well as the public needed to know exactly what a patent encompassed and where its proprietary boundaries started and ended in order to avoid duplicate property rights and contesting claims. In the context of modern patent law, patent law's materials have been mainly legal inscriptions, documents, files, classifications; although in some specific areas other non-semiotic representations inform the law, such as in the case of plant patents or other biological deposits.…”
Section: From Analog To Digital Materialities Of Patent Lawmentioning
confidence: 99%
“…Our second example is motivated by Kang (2012) qualitative study of the process of creation of an IPC class, to which the USPTO participated. Kang (2012) describes that the process of class creation was initiated because of a high number of incoming patents on the subject matter. Her main conclusion is that disputes regarding class delineation were resolved by evaluating the size of the newly created category under certain definitions.…”
Section: Three Examples Of Novel Classesmentioning
confidence: 99%
“…Our second example is motivated by Kang's (2012) qualitative study of the process of creation of an IPC class, to which the USPTO participated. Kang (2012) describes that the process of class creation was initiated because of a high number of incoming patents on the subject matter. Her main conclusion is that disputes regarding class delineation were resolved by evaluating the size of the newly created category under certain definitions.…”
Section: Class Numbermentioning
confidence: 99%